Reconfigurable Computing 2011
DOI: 10.1007/978-1-4614-0061-5_9
|View full text |Cite
|
Sign up to set email alerts
|

CRISP: Cutting Edge Reconfigurable ICs for Stream Processing

Abstract: The Cutting edge Reconfigurable ICs for Stream Processing (CRISP) project aims to create a highly scalable and dependable reconfigurable system concept for a wide range of tomorrow's streaming DSP applications. Within CRISP, a network-on-chip based many-core stream processor with dependability infrastructure and run-time resource management is devised, implemented, and manufactured to demonstrate a coarse-grained core-level reconfigurable system with scalable computing power, flexibility, and dependability. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…This coarse-grained reconfigurability of execution units is fast and done at run time. Instances of the tile-based multicore architecture template are demonstrated in Integrated Circuit (IC) [2,50] and Field-Programmable Gate Array (FPGA) [51].…”
Section: Kahrismamentioning
confidence: 99%
See 1 more Smart Citation
“…This coarse-grained reconfigurability of execution units is fast and done at run time. Instances of the tile-based multicore architecture template are demonstrated in Integrated Circuit (IC) [2,50] and Field-Programmable Gate Array (FPGA) [51].…”
Section: Kahrismamentioning
confidence: 99%
“…digital video processing, telecoms, and security applications) that need to process huge amounts of data in a short time would benefit from these attributes. Research projects such as MORPHEUS [1] and CRISP [2] have demonstrated the feasibility of such an approach and presented the benefit of parallel processing on real hardware prototypes. Providing a set of programming tools for respective cores is however not enough.…”
Section: Introductionmentioning
confidence: 99%
“…While there are other efforts as well to produce parallel code for execution on embedded or other special type platofrms, like MORPHEUS [8], CRISP [9] and MEGHA [10], they usually are tailored to the target architecture. MORPHEUS and CRISP attempt to leverage reconfigurable logic, while MEGHA targets manycore GPU systems starting with MAT-LAB.…”
Section: Introductionmentioning
confidence: 99%
“…The DeSyRe baseline SoCs consist of multiple heterogeneous processing cores, such as Xentium DSP cores [7], on-chip memory blocks, RISC processors, and custom accelerator blocks interconnected by a Network-onChip (NoC). Fault-tolerance extensions to existing NoC approaches [8,9] as implemented in [10,11], respectively, are considered in DeSyRe. The heterogeneous baseline SoC is implemented in the fault-prone part of the DeSyRe system.…”
Section: Baseline Implementation Platformmentioning
confidence: 99%